Comprehensive study on mutual interplay of multiple V-shaped ligands on the helical nature of a series of coordination polymers and their properties - Goswami, Arijit; Bala, Sukhen; Pachfule, Pradip; Mondal, Raju (Crystal Growth & Design, 2013)
{V-shaped ligands are commonly used for helical coordination polymer synthesis. However, employment of multiple V-shaped ligands does not always lead to a helical network. The mutual interplay of two V-shaped ligands, which is neither easily predictable nor well documented, plays a major role directing the self-assembly of the resultant network. We report here the construction of a series of novel coordination polymers {[Ni(OBA)(H2MDP)(H2O)]center dot(DMF)(3)}(n) (1),{[Ni(FBA)(H2MDP)]center dot(H2O)(3)center dot(DMF)\